Kajian Hadits Perbudakan dan Piagam Madinah: Sebuah Upaya dalam Merekontruksi Sistem Sosial - Fahmi Andaluzi (Jurnal Ilmiah Ilmu Ushuluddin, 2023)
Humans as the main actors in social action are a concern that cannot be underestimated when the problems that arise threaten the existence of human values. Islam comes as a founder that facilitates basic human rights. This paper seeks to explain the attitudes and efforts made by the Prophet towards slavery and his role in leading Medina in the midst of plurality and fanaticism at that time. In this study, the author uses a library research method by referring to several literatures such as hadith, books, and scientific articles. The results of this study indicate that the efforts made by the Prophet were essentially to abolish slavery, and the values of the policy in the Medina Charter are clearly to realize peace and harmony among mankind. At least there are several concepts that become stages to abolishing slavery, including treating slaves like their own brothers, encouraging and ordering freeing slaves, and ordering freeing slaves as sanctions for actions taken. While the values of the Medina Charter illustrate that the leadership and attitudes taken by the Prophet became the answer to the basic essence of human values. In the midst of the heterogeneous conditions of Medina society and frequent conflicts, the Prophet managed to overcome the problem by uniting and realizing peace through the establishment of the Medina Charter. The role played by the Prophet needs to be studied and researched in a broader scope to find out and apply Islamic attitudes and actions in overcoming humanitarian problems and social systems.